ISONIAZID-BASED SCHIFF’S BASES IN BONE CANCER STUDIES USING MG-63 CELL LINES - HEMALATHA, G. MUNI; THIRUNAVUKKARASU, KANDASAMY; KUMAR, C. RAMESH (International Journal of Applied Pharmaceutics, 2022)
Objective: Anticancer activities of Schiff bases S1 and S2 against MG-63 human osteosarcoma cells were performed and described using an in vitro evaluation employing cytotoxicity and apoptosis assay. Methods: MG-63 cells were used in an MTT assay to examine the effect of the compound on cell viability (S1 and S2). Cell morphologies and IC50 values were obtained. The acridine orange (AO)/ethidium bromide (EB) dual staining technique was used to determine the apoptosis process. Results: Our findings showed that synthesised S1 and S2 reduced MG-63 cell proliferation and induced apoptosis in a dose-dependent manner, implying that they could be used to treat bone cancer. Conclusion: Our findings showed that synthesised S1 and S2 reduced MG-63 cell proliferation and induced apoptosis in a dose-dependent manner, implying that they could be used to treat bone cancer.